2008
DOI: 10.1259/bjr/57705821
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous treatment of multiple basal cell carcinoma lesions

Abstract: We present a rare case of advanced basal cell carcinoma where multiple large lesions, located on the anterior chest wall and back, were treated simultaneously using tomotherapy (TomoTherapy HiArt; TomoTherapy Inc, Madison, WI). A 74-year-old man presented with seven to eight separate extensive lesions on his body, some with a duration of 7 years or more. The image-guidance component of tomotherapy allowed daily verification of the position of the target and critical structures, enabling accurate targeting in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…To our knowledge, this study is the largest cohort analysis of Helical TomoTherapy treatment of advanced non-melanoma skin cancer. Currently, only few case-reports have been published about the efficacy of TomoTherapy in skin cancer: one case of multiple BCCs treated simultaneously in the same patient, 30 one case of extensive BCC of the forehead and the scalp, 31 one case of sarcomatoid sarcoma of the scalp, 32 one case of recurrent eccrine mucinous adenocarcinoma of the scalp, 33 and three cases of skin malignancies without detail. 34 In our study, at a median 12-month follow-up, complete remission was observed in 88% of tumours: 100% in BCCs, 85.7% in CSCs, 80% in MCCs, and 75% in ACs.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this study is the largest cohort analysis of Helical TomoTherapy treatment of advanced non-melanoma skin cancer. Currently, only few case-reports have been published about the efficacy of TomoTherapy in skin cancer: one case of multiple BCCs treated simultaneously in the same patient, 30 one case of extensive BCC of the forehead and the scalp, 31 one case of sarcomatoid sarcoma of the scalp, 32 one case of recurrent eccrine mucinous adenocarcinoma of the scalp, 33 and three cases of skin malignancies without detail. 34 In our study, at a median 12-month follow-up, complete remission was observed in 88% of tumours: 100% in BCCs, 85.7% in CSCs, 80% in MCCs, and 75% in ACs.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this study is the largest cohort analysis of HT treatment of advanced non-melanoma skin cancer. Currently, only a few case reports have been published about the efficacy of tomotherapy for skin cancer: one case of multiple BCCs was treated simultaneously, one case of extensive BCC of the forehead and the scalp 32 , one case of sarcomatoid sarcoma of the scalp, one case of recurrent eccrine mucinous adenocarcinoma of the scalp, and three cases of skin malignancies [33][34][35][36] .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, one report mentioned as outcome after radiotherapy and tomotherapy that “the tumor showed an excellent response” without further elaboration. 10 …”
mentioning
confidence: 99%